2021
DOI: 10.1073/pnas.2103226118
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of fibrin γ-chain cross-linking by FXIIIa increases pulmonary embolism arising from murine inferior vena cava thrombi

Abstract: The onset of venous thromboembolism, including pulmonary embolism, represents a significant health burden affecting more than 1 million people annually worldwide. Current treatment options are based on anticoagulation, which is suboptimal for preventing further embolic events. In order to develop better treatments for thromboembolism, we sought to understand the structural and mechanical properties of blood clots and how this influences embolism in vivo. We developed a murine model in which fibrin γ-chain cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 42 publications
2
17
0
1
Order By: Relevance
“…This effect may be due to decreased fibrin crosslinking and/or decreased crosslinking of antifibrinolytic molecules (e.g., α 2 ‐antiplasmin) to fibrin 61 . Given differences in thrombus composition, enhanced PE in F13a −/− mice subjected to FeCl 3 ‐mediated thrombosis 11–13 or stasis‐induced VT (present study) strengthens evidence supporting a specific role of FXIII in PE. Longer‐term studies of thrombus resolution in FXIII‐deficient mice are needed to characterize the fate of VT and PE and reconcile apparent discrepancies in PE incidence between FXIII‐deficient humans and mice.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…This effect may be due to decreased fibrin crosslinking and/or decreased crosslinking of antifibrinolytic molecules (e.g., α 2 ‐antiplasmin) to fibrin 61 . Given differences in thrombus composition, enhanced PE in F13a −/− mice subjected to FeCl 3 ‐mediated thrombosis 11–13 or stasis‐induced VT (present study) strengthens evidence supporting a specific role of FXIII in PE. Longer‐term studies of thrombus resolution in FXIII‐deficient mice are needed to characterize the fate of VT and PE and reconcile apparent discrepancies in PE incidence between FXIII‐deficient humans and mice.…”
Section: Discussionsupporting
confidence: 78%
“…For example, compared to FXIIIsufficient mice (F13 +/+ ), FXIII-deficient mice (F13a −/− ) show increased bleeding following tail transection, but not saphenous vein puncture. 42 Moreover, mice with reduced FXIII antigen (F13a +/− or F13a −/− ) or delayed FXIII activation (Fibγ 390−396A ) have normal arterial thrombus formation and no measurable reflow events following FeCl 3 injury, 50,51 but reduced stasis-or stenosisinduced VT. 8,42 Collectively, these and other studies of FXIII function ( 8,(11)(12)(13)42,50,(52)(53)(54) and present work) suggest FXIII has nonoverlapping roles in venous and arterial thrombosis. Thus, a major aspect of the current work investigating VTE is the use of a mouse model that recapitulates key aspects of VTE in humans.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…However, recent studies from our lab showed associations between decreased average clot (and fiber) stiffness and increased occurrence of clot rupture. 55,84 The association between these properties requires further investigation.…”
Section: Rupturementioning
confidence: 99%